The use of C-reactive protein in case of preterm labor with intact membranes - Ratsiatosika, Tanjona A.; Romuald, Randriamahavonjy; Valérie, Rajaonarivony Marie; Lantonirina, Rainibarijaona A.; Tahiana, Rakotonirainy; Ando-Miora, Rakotonirina; la Croix, Rasolonjatovo Jean de (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preterm labor, defined as delivery between 22 and 37WA, is the leading cause of perinatal morbidity and mortality. Through this study, we wanted to know if the high CRP rate in preterm labor with intact membranes could be a risk factor for poor prognosis on pregnancy and the newborn. Methods: We conducted a prospective cohort study from November 1, 2018 to April 31, 2019 at Befelatanana University Hospital of Gynecology-Obstetrics on singleton pregnancies with preterm labor and intact membranes. The population is divided in two groups according to the rate of CRP and we have chosen as a pathological threshold a CRP ≥7 mg/l. Results: We included 71 cases of MAP over 1735 births, or 4.09%, of which 47% had a CRP≥7mg / l (group I) and 51% a CRP <7mg / l (group II). There was a significant difference in the persistence of uterine contraction after 48h of tocolysis in group I and II [p = 0.0013, RR 5.20 (1.63-16.55)] as well as within of delivery (7.68±5.33 versus 21.36±11.30 days, p <0.05). There was no difference in the occurrence of neonatal asphyxia and neonatal infection between the 2 groups. However, the risk of prematurity is high in the group with a high CRP level [RR 1.34 (1.06-1.70)] (p = 0.02). Conclusions: In the case of preterm labor with intact membrane, CRP is a determinant of delivery delay, failure of tocolysis, and occurrence of preterm delivery.